Heart failure virtual consultation: caters for frailer, multimorbid and remote patients - Mark Ledwidge; Matthew Barrett; Bethany Wong; Joseph McCambridge; Lisa McCudden; Ronan Fawsitt; Joseph J Gallagher; Kenneth McDonald (Open Heart, 2023)
Background: The heart failure (HF) virtual consultation (VC) is an eHealth tool for delivery of peer-to-peer specialist advice to general practitioners (GPs) to discuss HF diagnosis/management. We aim to investigate the impact of the VC service on onward referral rate and quality of assessment by GPs, as well as assess VC patient characteristics; Clinical Frailty Score (CSF), age and morbidity.Methods: This prospective observational study collected VC data on: demographics, comorbidity, frailty, referral indication, the impact of VC on clinical care and the GP response to the question ‘what would you have done without the VC service’. We compared patient characteristics to a control population of patients attending the HF unit (HFU) (n=118).Reults: Between 2015 and 2021, 1681 VC cases were discussed. The majority of cases were discussed from remote areas (75%). Rediscussion cases increased from 0% to 34%. VC patients were older (76.2 (±11.3) vs 73.1 (±12.5) years, p<0.05), more frail (CSF=3.8 (±1.7) vs 3 (±1.6), p<0.01) and multimorbid (number of comorbidities=7.1 (±3.4) vs 3.8 (±1.9), p<0.001) compared with patients attending the HFU. Without the VC, 93% of cases would have been referred to face-to-face hospital services. Instead, VC resulted in only 9% of cases being referred to hospital services. The remainder of cases were managed by the VC service, in a shared GP-specialist approach. GP use of natriuretic peptide (NP) increased from 0% in 2015–2016 to 63% in 2021 and use of TTE increased from 0% in 2015–2016 to 69% by 2021.Conclusions: The VC service provides a platform for case discussion in particular for older, frailer patients and reduces onward hospital referrals. This may facilitate early diagnosis and management of suspected HF in the current era of long outpatient waiting times. The quality of community HF assessment improved as indicated by increased use of NP/TTE by GPs.